12-(n-3)=

Simple and best practice solution for 12-(n-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-(n-3)= equation:


Simplifying
12 + -1(n + -3) = 0

Reorder the terms:
12 + -1(-3 + n) = 0
12 + (-3 * -1 + n * -1) = 0
12 + (3 + -1n) = 0

Combine like terms: 12 + 3 = 15
15 + -1n = 0

Solving
15 + -1n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + -1n = 0 + -15

Combine like terms: 15 + -15 = 0
0 + -1n = 0 + -15
-1n = 0 + -15

Combine like terms: 0 + -15 = -15
-1n = -15

Divide each side by '-1'.
n = 15

Simplifying
n = 15

See similar equations:

| 7=2x+11 | | R+4=20 | | z+4.9=8.8 | | 7x+60=x-6 | | 45=-5(k+4) | | 2/5x-=1/5x-12 | | 2sin^2-3cos+1=0 | | 11a^2+2a-17=0 | | 5a+6a=-6+8a | | 360=(x+40)+(4x+70)+(2x+110) | | x+47=54 | | 4x^2-2-8w=-6x | | -14x+1=21 | | 360=(x+50)+(2x+80)+(4x+20) | | x^4-5x^3-2x^2-3x-9= | | 5y-(3y+8)=3-(7y-9) | | 5(x-1)=3(2-x)-5 | | x+52=61 | | 11v-2v=54 | | x+78=86 | | 90x^2-63xy+18x=0 | | 7=m/125 | | -3.5b-1.75c= | | 4X+20=25-x | | x-2(-2x+20)=20 | | c/2=-14 | | X^2+27x-18=0 | | d=7.25t | | 1.1x=94000 | | -4(2t+5)=-60 | | 24x+7x=19 | | =11x+5y-30z |

Equations solver categories